Aetiological overlap between anxiety and attention deficit hyperactivity symptom dimensions in adolescence. (8th September 2014) - Michelini, Giorgia; Eley, Thalia C.; Gregory, Alice M.; McAdams, Tom A.
Abstract : Background: Anxiety and attention‐deficit/hyperactivity (ADH) problems are common in adolescence, often co‐occur, and are characterised by high heterogeneity in their phenotypic expressions. Although it is known that anxiety and ADH problems correlate, the relationships between subtypes of anxiety and ADH problems have been scarcely investigated. Methods: Using a large population sample of adolescent twins and siblings we explored the phenotypic and aetiological association between anxiety subtypes (panic/agoraphobia, separation anxiety, social anxiety, physical injury fears, obsessive‐compulsive symptoms and generalised anxiety) and the two ADH dimensions (attention problems and hyperactivity/impulsivity). Both phenotypes were assessed using self‐report questionnaires. Results: The association between ADH problems and anxiety could be entirely attributed to attention problems, not hyperactivity/impulsivity. Most of the correlations between anxiety subtypes and attention problems showed an approximately equal role of genetic and nonshared environmental factors. Conclusions: The high heterogeneity within anxiety and ADH problems should be taken into account in order to better understand comorbidity between them.